Osteosarcoma of the jaw - Carretero Ancelmo, Daniel A. (2011)
Osteosarcoma is a malignant neoplasia, uncommon, which may originate in the bone of the oral cavity.Bone malignant tumors are often found in the epiphysis of long bones (femur, tibia or perone). We report the case of a male patient aged 27 with mandibular osteosarcoma that was treated with wide resection and chemotherapy in a first phase and the control after 3 months without evidence of recurrence.